2018
DOI: 10.1108/cg-11-2017-0271
|View full text |Cite
|
Sign up to set email alerts
|

Related party transactions, corporate governance and earnings management

Abstract: Purpose Following the contingency perspective, this paper aims to examine if a good corporate governance structure is able to reduce earnings management made through related party transactions. The authors expect that a high-quality corporate governance influences private benefit acquisition and reduces the positive association between related party transactions and earnings management. Design/methodology/approach A two-stage least squares instrumental variable approach is used to further address endogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 158 publications
2
39
0
1
Order By: Relevance
“…A study conducted by Mita & Utama, 2017;Yang, Kweh, & Lin, 2014 documented that related party transactions lead to higher earnings quality. In contrast, other studies reported that related party transactions do not lead to earnings quality in listed non-financial firms by (Gordon & Elaine Hen, 2017;Kim & Yoo, 2017;Marchini, Mazza, & Medioli, 2018;Saleh, Munir, Jaffar, & Yatim, 2013).…”
Section: Related Party Transactions and Real Earnings Managementmentioning
confidence: 74%
See 1 more Smart Citation
“…A study conducted by Mita & Utama, 2017;Yang, Kweh, & Lin, 2014 documented that related party transactions lead to higher earnings quality. In contrast, other studies reported that related party transactions do not lead to earnings quality in listed non-financial firms by (Gordon & Elaine Hen, 2017;Kim & Yoo, 2017;Marchini, Mazza, & Medioli, 2018;Saleh, Munir, Jaffar, & Yatim, 2013).…”
Section: Related Party Transactions and Real Earnings Managementmentioning
confidence: 74%
“…Family affiliation is measured by the percentage of common stock ownership by founding family members (Achleitner et al, 2014;Guo & Ma, 2015;Tian, Yang, & Yu, 2018). Also, related party transactions are measured by the natural logarithm of annual transaction value and were derived from firms' financial reports (Marchini et al, 2018;Shin et al, 2019). The study further used control variables that previously shown to be effective in enhancing the earnings quality.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, due to the inconsistencies and biases in these theories, Pizzo (2013) suggested adopting a pragmatic approach using the contingency theory. This theory has also been employed by scholars in analysing the relationship between sales and earnings in RPT (Marchini et al, 2018a). Besides, the analysis of the mandatory/enabling theory is needed to justify the rationale of having a minimum standard for corporate law if the market fails to protect the shareholders (Ramsay, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ketika transaksi pihak berelasi dimotivasi dengan kepentingan untuk mengambil keuntungan pribadi maka akan merugikan perusahaan atau pemegang saham (Utama & Utama, 2013;Wong et al, 2015). Nilai perusahaan dapat menurun dengan adanya transaksi pihak berelasi yang dimotivasi sebagai sarana untuk oportunisme manajerial, seperti manajemen laba oportunistik, tunneling, dan pengambilan kekayaan dari pemegang saham (Wong et al, 2015;Chen et al, 2017;Marchini et al, 2018).…”
Section: Pendahuluanunclassified